Teaching English in times of the national bilingual program in some state schools: linguistic and pedagogical factors - Maturana Patarroyo, Liliana María (Colombian Applied Linguistics Journal, 2011)
This mixed-interdisciplinary study was conducted in four state schools in Medellin-Colombia with the participation of 12 teachers and 111 students from 3rd, 4th and 5th grades. Data gathering techniques used were a semi structured interview administered to the 12 teachers and a battery of six psycholinguistic tests administered to the students. This paper addresses qualitative data from the interview and discusses, from a reflective and interpretative perspective, linguistic and pedagogical factors that affect the English teaching and learning processes for a 12-primary-teacher group. These factors emerged essential for the establishment of pedagogical relationships amongst teachers, students and the English language; likewise, the necessity of informed and continuous teacher professional development programmes as part of linguistic policies becomes manifest.